Animals in summer - McCauley, Jane R., 1947- (Washington, D.C. : National Geographic Society, 1988)
Observes the behavior of several animals during the summer months.
Bibliography: p. [34].
Keywords: Animals -- Summering -- Juvenile literature; Animals -- Habits and behavior